ISLAMIC FINANCING: A PANACEA TO SMALL AND MEDIUM SCALE ENTERPRISES FINANCING PROBLEMS IN NIGERIA - Isah Bazza, Mohammed; Yusuf Maiwada, Bashir; Ahmad Daneji, Bashir (European Scientific Journal, ESJ, 2014)
Small and Medium Scale Enterprises (SMEs) play significant role insustainable economic growth and development, especially in developingeconomies. In Nigeria, SMEs are facing financing problems which hindertheir survival as a result they could not play the expected roles in theeconomy. The objective of this paper is to explore the use of IslamicFinancing in solving SMEs financing problems. The study is exploratory;hence various literatures were sourced, reviewed and discussed. It was foundthat the conventional sources of financing SMEs are grossly inaccessible,costly and not feasible. As a new source of financing in the country, Islamicfinancing is feasible, though inadequate but relatively accessible andcostless. One of the recommendations is that financial institutions should beadopting Islamic mode of finaning when financing SMEs in the country as itwill go a long way in solving SMEs financing problems.